Branding simbólico e hibridación: una aproximación en la intersección cultural fronteriza México-Estados Unidos de América: el caso de Ciudad Juárez-El Paso - Patricia Ramos Rubio; Isabel Zizaldra-Hernández (Nóesis)
The article examines the inclusion of symbolic branding hybridization in the Mexico-United States of America border from the perspective of an open and poly significant binational region where complex processes and sometimes conflicting groups of interest and stakeholders become articulated. Using hybridization as a tool, it's possible to establish a common starting point conceiving branding within the dichotomy, as the attribute of a product that leaves a lasting impression on the minds of consumers and which turns the brand into a cultural icon directly impacting the thoughts and attitudes of people. This paper thrives to approach common knowledge of the major commercial brands that have taken root in the region of Ciudad Juarez-El Paso by contrasting the commercial culture from the per136 172 11 Vol. 21 ¿ número 41 ¿ 2012 spective of boundary and crossborder conditions. The investigation presents a quantitative methodology divided in three stages: The 1st stage is office work by reviewing the literature; stage 2, approaching the phenomenon through network theory (ARS), linking the EGR Theory Alderfer on resource dependency; and a stage 3 with the implementation, under the EGR (Existence, Value and Growth) criteria, of 105 surveys, where 18 items where considered for evaluation. Instrumentation is done through the snowball method and the main results of hybridization are: Office Depot, Coca-Cola and Colgate.